An Explorative Analysis of the Relationship between Legal Status Event Data and Patent Quality Metrics - Andrea CELONE (Communications of International Proceedings, 2020)
The work presents an explorative analysis of the relationship between legal status event data and patent quality metrics. Indeed, legal status event data might disclose a list of events that have changed the likelihood of exploitation of a patented technology, and consequently its quality. A classification based on 124 categories of events is presented and such categories are studied for a sample of 118,850 patent applications. The correlation analysis between legal status event data and traditional patent quality metrics confirms the usefulness and the potential of legal status event data, since the occurrence of specific events is related to the quality associated to a patented technology.